2018
DOI: 10.1128/iai.00450-18
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Lipoprotein and Lipoglycan Binding to Toll-Like Receptor 2 Correlates with Agonist Activity and Functional Outcomes

Abstract: causes persistent infection due to its ability to evade host immune responses. induces Toll-like receptor 2 (TLR2) signaling, which influences immune responses to TLR2 agonists expressed by include lipoproteins (e.g., LprG), the glycolipid phosphatidylinositol mannoside 6 (PIM6), and the lipoglycan lipomannan (LM). Another lipoglycan, mannose-capped lipoarabinomannan (ManLAM), lacks TLR2 agonist activity. In contrast, PILAM, from , does have TLR2 agonist activity. Our understanding of how lipoproteins and lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…Surface plasmon resonance (SPR) studies using purified LprG and triacylated lipids including LAM further confirmed this molecular interaction and revealed a secondary sugar‐binding site outside of the hydrophobic pocket, resulting in a particularly high affinity of LprG for LAMs (Shukla et al , ). Very recent studies in addition revealed molecular interactions of purified LprG with TLR2 (Shukla et al , ). Virulence of M. tuberculosis Δ lprG in BALB/c mice was clearly attenuated and the mutant exhibits impaired macrophage entry and fails to inhibit phagosome–lysosome fusion (Bigi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) studies using purified LprG and triacylated lipids including LAM further confirmed this molecular interaction and revealed a secondary sugar‐binding site outside of the hydrophobic pocket, resulting in a particularly high affinity of LprG for LAMs (Shukla et al , ). Very recent studies in addition revealed molecular interactions of purified LprG with TLR2 (Shukla et al , ). Virulence of M. tuberculosis Δ lprG in BALB/c mice was clearly attenuated and the mutant exhibits impaired macrophage entry and fails to inhibit phagosome–lysosome fusion (Bigi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…LAM and LM both play an important role in the modulation of the host’s immune defences ( Schlesinger et al, 1994 , Shukla et al, 2018 ). A variety of LAM caps exist, each affecting the immune response in different ways.…”
Section: The Cell Wall Corementioning
confidence: 99%
“…TLRs 2, 4, and 9 reportedly recognize mycobacteria [14][15][16][17]. TLR2 recognizes lipoproteins, peptidoglycan, and glycolipids (e.g., LAM, LM, and PIMs) [18,19]. With respect to NTM infection, TLR2 (not TLR4) has been reported to recognize Mycobacterium avium in vitro [20].…”
Section: Innate Immune Response To Ntm Infectionmentioning
confidence: 99%